Metabotropic glutamate receptor 2 inhibits thalamically-driven glutamate and dopamine release in the dorsal striatum. (1st May 2017) - Johnson, Kari A.; Mateo, Yolanda; Lovinger, David M.
Abstract: The striatum plays critical roles in action control and cognition, and activity of striatal neurons is driven by glutamatergic input. Inhibition of glutamatergic inputs to projection neurons and interneurons of the striatum by presynaptic G protein-coupled receptors (GPCRs) stands to modulate striatal output and striatum-dependent behaviors. Despite knowledge that a substantial number of glutamatergic inputs to striatal neurons originate in the thalamus, most electrophysiological studies assessing GPCR modulation do not differentiate between effects on corticostriatal and thalamostriatal transmission, and synaptic inhibition is frequently assumed to be mediated by activation of GPCRs on corticostriatal terminals. We used optogenetic techniques and recently-discovered pharmacological tools to dissect the effects of a prominent presynaptic GPCR, metabotropic glutamate receptor 2 (mGlu2 ), on corticostriatal vs. thalamostriatal transmission. We found that an agonist of mGlu2 and mGlu3 induces long-term depression (LTD) at synapses onto MSNs from both the cortex and the thalamus. Thalamostriatal LTD is selectively blocked by an mGlu2 -selective negative allosteric modulator and reversed by application of an antagonist following LTD induction. Activation of mGlu2/3 also induces LTD of thalamostriatal transmission in striatal cholinergic interneurons (CINs), and pharmacological activation of mGlu2/3 or selective activation of mGlu2 inhibits CIN-mediated dopamine release evoked by selective stimulation of thalamostriatal inputs. Thus, mGlu2 activation exerts effects on striatal physiology that extend beyond modulation of corticostriatal synapses, and has the potential to influence cognition and striatum-related disorders via inhibition of thalamus-derived glutamate and dopamine release. Highlights: The mGlu2/3 agonist LY379268 induces LTD of corticostriatal and thalamostriatal transmission in the dorsal striatum. LTD induction is selectively blocked by a negative allosteric modulator of mGlu2. Thalamostriatal LTD is observed at synapses on both medium spiny neurons and cholinergic interneurons. mGlu2 activation reduces phasic dopamine release driven by thalamostriatal excitation of cholinergic interneurons.